2000
DOI: 10.1007/pl00008406
|View full text |Cite
|
Sign up to set email alerts
|

Hospital stay and short-term follow-up of children of drug-abusing mothers born in an urban community hospital – a retrospective review

Abstract: New ways to ensure better co-ordination between paediatricians and the social services (inside and outside the hospital) should be developed to shorten the neonatal hospitalisation period and improve the quality of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Nevertheless, some infants spent up to 20 further days on the neonatal unit because the social circumstances of their mother prevented discharge. Others (Payot & Berner 2000) have also reported that the length of neonatal unit stay may be increased by non‐medical problems; in that study the average extension was 8 days. To minimize neonatal unit stay, those data argue strongly for pre‐delivery planning meetings to ensure appropriate carer(s) and venue of care following discharge are identified well before the infant is to be discharged.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Nevertheless, some infants spent up to 20 further days on the neonatal unit because the social circumstances of their mother prevented discharge. Others (Payot & Berner 2000) have also reported that the length of neonatal unit stay may be increased by non‐medical problems; in that study the average extension was 8 days. To minimize neonatal unit stay, those data argue strongly for pre‐delivery planning meetings to ensure appropriate carer(s) and venue of care following discharge are identified well before the infant is to be discharged.…”
Section: Discussionmentioning
confidence: 78%
“…This form of drug use then has important implications for resource utilization. The majority of women who take methadone have been enrolled in methadone prescribing programmes (Payot & Berner 2000) and therefore have had contact with health‐care professionals. Such contact should offer the opportunity to counsel women regarding the adverse effects of taking additional substances with methadone during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor which determines duration of hospital stay is whether the social circumstances of the mother prevents discharge; we previously noted this could extend admission by 20 days [10]. Others [14] have also reported that the length of neonatal unit stay may be increased by non-medical problems. In this study, similar proportions of infants were discharged home with their mothers and the maternal demographics of the two groups did not differ significantly.…”
Section: Discussionmentioning
confidence: 93%
“…Population information, however, is crucial for regional planning and for the implementation and evaluation of appropriate services because variations in practice may have a profound impact on health‐care expenditure for these patients 1 . Ascertaining the number and detail of such pregnancies is important because apart from social issues, the offspring of drug‐using mothers are at a considerably increased risk of problems such as neonatal abstinence syndrome (NAS), prematurity, low birthweight and poor neurodevelopmental outcome 2–7 …”
mentioning
confidence: 99%